Temperature tolerance of juvenile tiger-tail seahorse, Hippocampus comes. - Fillaro, Bea Camille Nopueto
An experiment was carried out to determine the low and high temperatures that could be tolerated by the juvenile seahorse Hippocampus comes (3 months old). The low temperature levels tested were 16, 19 and 22 degress centigrade. The high temperature level tested were 32, 35 and 38 degrees centigrade. Ambient water temperature of 26-29 degrees centigrade served as the control. Seahorses were acllimized for 1 h prior to transfer to various experimental temperatures. For H. comes, 5 L plastic containers were used with 10 seahorses per container. The experimental containers were floated in a 1 tonne fiberglass tank filled with 18cm of water, which served as water bath, to maintain the desired water temperature inside the containers. There were three replicates per treatment. Survival of the seahorses was monitored every hour for 96 h. Results showed that at the lowest temperature of 16 degrees centigrade, a survival of 76.7 percent was observed on the 24th h. On the 48 h percentage survival dropped to 60 percent. After 96 h only 56.7 percent of seahorses remained alive. On the ohter hand, 100 percent survival of juvenile seahorses was obtained on moderately low temperatures of 19 degrees centigrade and 22 degrees centigrade. At moderately warm temperature of 32 degrees centigrade, there was 100 percent survival of the juvenile H. comes up to the 66th h of culture. However on the 72nd h survival dropped to 96.7 percent which was maintained up to the end of the experiment. At a warm temperature of 35 degrees centigrade only 20 percent of the juvenile seahorses remained alive on the 6th h of exposure and the remaining seahorses died after 12th h. On othe other hand all H. comes juveniles died within an hour of exposure to a very high temperature of 38 degrees centigrade.